MODEL PENGARUH ANGGARAN BIAYA ERA COVID-19 TERHADAP INFORMASI AKUNTANSI PERTANGGUNG JAWABAN - Lesi Hertati; Rilla Gantino; Lilis Puspitawati; Meifida Ilyas (Universitas Tridinanti, 2020)
ABSTRACK The Covid-19 Era budget is one of the government's steps to provide funds to tackle the pandemic by making adjustments or saving on spending by ministries / agencies for 2020. The budget for preventing Covid-19 is budgeted by reducing the allocation of costs to other posts (Refocussing and Reallocation Budget). Flexibility creates opportunities both in terms of timing and size of issuance according to local government financial conditions. Adjustment of the precautionary principle by taking into account the risks and costs, the smallest target achievement is decreasing, but the number of positive patients with Covid-19 is still increasing, making the implementation of official travel difficult, in the end it will affect the results of the results at the end of 2020 impact on responsible accounting information. This study focuses on the Covid-19 cost budget on responsibility accounting information. Survey on local government work units in 3 (three) major cities, namely Palembang, Jakarta, Bandung. The population in this study were 108 local work units, which returned 80 defective samples, the remaining 75 samples were ready to be processed. The data analysis technique used in this study was SEM PLS using descriptive and verification methods. The results of this study indicate that the Covid-19 Era budget affects accountability accounting information.Keyword : Budget Era Covid-19, Accountability Accounting Information